Research Hotspots and Trends in Sustainable Livelihood: A Bibliometric Analysis - Changyan Cai; Lim, Beatrice Fui Yee; Kasim Mansur (Asian Scholars Network, 2023)
Sustainable livelihood is a hot topic of study among scholars. Based on the Web of Science (SCI-Expanded, SSCI) database, this article conducts a bibliometric analysis of sustainable livelihoods research from the perspectives of document quantity, authorship, journals, and keyword clustering. The study found that scholars' research on this field has gone from inception to explosion and then to stability over the past few decades. The highest number of publications came from China, the USA, and England, and the journal with the most publications was "Sustainability". Co-authorship trends among sustainable livelihood authors were quite obvious. Articles have been highly cited, with a total of 31,635 citations and an average citation frequency of 20 times per article. Through the analysis of the keyword clustering network and emerging keywords, the research hotspots and trends of sustainable livelihoods can be roughly divided into theoretical and methodological approaches, policy and management, ecological environment, and rural livelihoods.